Ultraviolet pump-probe photodissociation spectroscopy of electron-rotation coupling in diatomics - Liu, Yan Rong; Kimberg, Victor; Wu, Yong; Wang, Jian Guo; Vendrell, Oriol; Zhang, Song Bin (The journal of physical chemistry letters, 2021)
The electronic angular momentum projected onto the diatomic axis couples with the angular momentum of the nuclei, significantly affecting the rotational motion of the system under electronic excitations by intense lasers. In this letter, we propose a pump-probe photodissociation scheme for an accurate determination of electron-rotation coupling effects induced by the strong fields. As a showcase we study the CH+ molecule excited by a short intense ultraviolet pump pulse to the A1Π state, which triggers coupled rovibrational dynamics. The dynamics is observed by measuring the kinetic energy release and angular resolved photofragmentation upon photodissociation induced by the time-delayed probe pulse populating the C1Σ+ state. Simulations of the rovibrational dynamics unravel clear fingerprints of the electron-rotation coupling effects that can be observed experimentally. The proposed pump-probe scheme opens new possibilities for the study of ultrafast dynamics following valence electronic transitions with current laser technology, and possible applications are also discussed.
Gesehen am 13.08.2021